Electron transfer quenching of rhodamine 6G by N-methylpyrrole is an unproductive process in the photocatalytic heterobiaryl cross-coupling reaction - Tan, Yi Zhen (2022)
In the heterobiaryl cross-coupling reaction between aryl halides (Ar-X) and N-methylpyrrole (N-MP) catalyzed by rhodamine 6G (Rh6G+) under irradiation with visible light, a highly active and long-lived (millisecond time range) rhodamine 6G radical (Rh6G•) is formed upon electron transfer from N,N-diisopropylethylamine (DIPEA) to Rh6G+. In this study, we utilized steady-state and time-resolved spectroscopy techniques to demonstrate the existence of another electron-transfer process occurring from the relatively electron-rich N-MP to photoexcited Rh6G+ that was neglected in the previous reports. In this case, the radical Rh6G• formed is short-lived and undergoes rapid recombination (nanosecond time-range), rendering it ineffective in reducing Ar-X to aryl radicals Ar• that can subsequently be trapped by N-MP. This is further demonstrated via two model reactions involving 4'-bromoacetophenone and 1,3,5-tribromobenzene with insignificant product yields after visible-light irradiation in the absence of DIPEA. The unproductive quenching of photoexcited Rh6G+ by N-MP leads to a lower concentration of photocatalyst available for competitive charge transfer with DIPEA and hence decreases the efficiency of the cross-coupling reaction.